Artificial intelligence application in counselling practices. A multigroup analysis of acceptance and awareness using gender and professional rank - Ofem, Usani Joseph; Anake, Pauline Mbua; Abuo, Cyril Bisong; Ukatu, James Omaji; Etta, Eugene Onor (Frontiers in Digital Health, 2025)
IntroductionArtificial intelligence (AI) has emerged as a transformative tool in various professional domains, including counselling, where it offers innovative ways to enhance service delivery and client outcomes. Despite its potential, research on AI in counselling practices often focuses on its technical applications, with limited attention to the interplay between awareness, acceptance, and application. This study analyses how professional counsellors apply artificial intelligence in counselling practices using the nexus between awareness and application through acceptance of AI with gender and professional rank as group.MethodA total of 5,432 professional counsellors were selected for the study. Data collection was conducted online to ensure a wide reach. The research instruments underwent validity checks, demonstrating high content and factorial validity. Convergent and discriminant validity were confirmed using the Average Variance Extracted (AVE) and Fornel-Larcker criterion.ResultsThe findings revealed that professional counsellors exhibited high levels of awareness, acceptability, and application of AI in their counselling practices. Acceptance played a positive mediating role in the relationship between awareness and application. However, male practitioners and professors displayed stronger awareness, acceptance, and application of AI tools compared to their counterparts.ConclusionThe study highlights the significant role of acceptance in bridging awareness and application of AI in counselling practices. It underscores the importance of addressing gender and professional rank disparities to ensure equitable adoption and utilization of AI tools. The findings offer valuable insights for policymakers in promoting the integration of AI in counselling to enhance professional practices.